Comments on the investment-uncertainty relationship in a real option model - Nunzio Cappuccio; Michele Moretto (Fondazione Eni Enrico Mattei (FEEM), 2001)
The paper considers the problem of evaluating the probability of investing in a capital-investment project as a measure of the uncertainty-investment relationship in a real option model. By the use of the contingent claims analysis the opportunity to invest is modelled as an American call option with expiring time. We show that an increase in uncertainty of the project may actually have positive or negative effects on the probability of investing depending on which market parameters are called to restore the asset price equilibrium condition.
Keywords: C6; E2; 330; Investment; uncertainty; real options; Betriebliche Investitionstheorie; Optionsgeschäft; Theorie; Entscheidung bei Unsicherheit